The Role of Mindfulness-Based Interventions in Treating Depression among Population Subgroups - Saiuk, Nazarii; Kołodziej, Magdalena; Kozicz, Michał Andrzej; Mądry, Wojciech; Mazurkiewicz, Aleksandra; Męczyńska, Joanna; Seredyński, Tomasz; Wojciechowska, Adriana; Marcicka, Justyna; Salasa, Weronika (Journal of Education, Health and Sport, 2024)
Introduction Major depressive disorder (MDD) is one of the most common psychiatric disorders, with its prevalence on the rise. The use of mindfulness-based interventions (MBIs), primarily including mindfulness-based cognitive therapy (MBCT) and mindfulness-based stress reduction (MBSR), in MDD is scientifically justified. But will every population subgroup benefit from such an approach? Aim of the study The aim of our study is to analyze, based on the latest scientific findings, the effects of MBIs within specific subgroups of patients suffering from depression, including adolescents, elderly patients, cancer patients, individuals experiencing postnatal and perinatal depression, and patients with chronic pain. Additionally, we sought to summarize the current knowledge regarding the structural and functional effects of MBIs on the human brain. Materials and methods We conducted a comprehensive search of scientific databases including PubMed and Google Scholar to identify relevant articles focusing on MBIs and their effects on treating depression within various subgroups. Additionally, we performed a review of literature available on PubMed and Google Scholar to summarize the current knowledge regarding the impact of MBIs on the human brain. Conclusions Across various subgroups MBIs show promise in reducing depressive symptoms, indicating their potential as adjunctive treatments or preventive measures. While longer intervention durations are associated with larger effects, further research is needed to establish a solid evidence base, particularly in older populations and cancer patients with different cancer types.